2017
DOI: 10.1175/wcas-d-16-0059.1
|View full text |Cite
|
Sign up to set email alerts
|

Is Tropical Cyclone Surge, Not Intensity, What Kills So Many People in South Asia?

Abstract: This paper statistically examines the hypothesis that the level of storm surge, not storm intensity, is primarily responsible for the large number of tropical cyclone fatalities in South Asia. Because the potential causal link between intensity and surge can confound statistical inference, the authors develop two fatality models using different assumptions on the relationship between storm surge and intensity. The authors find evidence that storm surge is a primary killer of people in South Asia relative to st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Along coastal areas, a storm surge is often the greatest threat to life and property (e.g. Irish et al ., ; Seo and Bakkensen, ), followed by flooding and landslips caused by the heavy rain (e.g. Marks and Shay, ; Rappaport, ; Chien and Kuo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Along coastal areas, a storm surge is often the greatest threat to life and property (e.g. Irish et al ., ; Seo and Bakkensen, ), followed by flooding and landslips caused by the heavy rain (e.g. Marks and Shay, ; Rappaport, ; Chien and Kuo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Storm surge is a phenomenon of rising water height of the waves because of high speed winds and low pressure associated with the cyclones resulting in coastal floods. Previous experiences reveal that most of cyclone related deaths in Bangladesh were due to surges associated with the storms (Khalil, 1992;Zachry et al, 2015;Seo and Bakkensen, 2016). UNICEF (1993) cyclone evaluatio n team during their post cyclone (1991) survey observed that almost all deaths have been as a result of drowning from the tidal wave that accompanied the cyclone.…”
Section: Storm Surgementioning
confidence: 99%
“…Between 1980 and 2009 cyclones affected 466 million people, resulting in death of 412,644 and injury to 290,654 with less developed nations in Asia experiencing the maximum mortality and injury (Doocy et al, 2013). On an average, a tropical storm landfall in the north Indian Ocean results in death of about 2000 persons which is much higher compared to average fatalities per landfall in any other ocean basin of the world (Seo and Bakkensen, 2016).…”
mentioning
confidence: 94%
“…On the other hand, adaptation research over the past two decades has reported high potential and observed net benefits of adaptation strategies and measures to global warming in natural resource intensive industries (Seo and Mendelsohn ; Seo , , , ), in sea level rises (Yohe and Schlesinger ; Ng and Mendelsohn ), in heat‐related or cold‐related fatalities (Barreca et al ), and in extreme events such as tropical cyclone‐caused fatalities (Seo ; Seo and Bakkensen ). In many world regions, adaptation will make harmful effects of global warming much less severe.…”
Section: Future Directions Of Global Warming Negotiationsmentioning
confidence: 99%